Trimethylamine functionalized radiation-induced grafted polyamide 6 fibers for p-nitrophenol adsorption - M.Saber, Shihab Ezzuldin; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain; Choong, Thomas S. Y.; Teo, Ming Ting (Springer, 2021)
The method of pre-irradiation grafting was used with the aid of electron beam (EB) accelerator to accomplish the grafting of polyamide 6 fibers (PA6) with glycidyl methacrylate (GMA). The extent to which GMA was grafted on PA6 was found to be markedly influenced by the absorbed dose of radiation and the reaction time of grafting. Trimethylamine (TMA) was afterwards employed for the functionalization of GMA-grafted fibers (PA6-g-GMA). A range of analyses (e.g., FTIR, FESEM, XRD, BET, and pHpzc) were carried out to determine the physiochemical and morphological properties of the fibrous adsorbent. p-Nitrophenol (PNP) adsorption from aqueous solution was conducted with the resulting TMA-(PA6-g-GMA) adsorbent. The adsorption behaviour of PNP on the fibrous adsorbent was clarified by investigating the adsorption kinetics and isotherm. According to the results, the adsorption of PNP on TMA-(PA6-g-GMA) reflected the pseudo-second order model. Meanwhile, the isotherm analysis revealed that the best description of the equilibrium data was provided by Redlich–Peterson model, followed closely by Langmuir isotherm model. The achieved adsorption capacity was highest at 176.036 mg/g. Moreover, the adsorption was indicated by the thermodynamic analysis to be spontaneous and exothermic. Regeneration and recycling of the adsorbent was possible for a minimum of five cycles with no reduction in adsorption capacity. It was concluded that the fibrous adsorbent could have applications for the removal of PNP at industrial pilot scale.